Rhythms of Kinabalu 2022 “Coming Back Stronger”: A Review - Shahnaz Mohd Baldev Shah; Khairul Anuar Samsuddin (Wacana Seni Journal of Arts Discourse, 2024)
This article reviews the Rhythms of Kinabalu 2022 from the dual perspective of management and performance. Ever since its commencement in 2011, Rhythms of Kinabalu has been a yearly large-scale event organised by the National Department for Culture and Arts under the Ministry of Tourism, Arts and Culture Malaysia along with other collaborative bodies. The aim of this festival is to showcase the diversity and uniqueness of the dances, arts, and music in Sabah for the purpose of their continued popularity, relevance, and sustainability. As such, the review examines the current nature of festival, paying attention to the various categories of performances and performers in Rhythms of Kinabalu 2022 as well as the favoured and less favoured performances and/or artists as indicated by viewer turnouts of the live shows. At the same time, the article seeks to understand the local audiences’ reception and/or reaction towards the event and its many shows to signal the current festivalgoers’ taste and preference of the performing arts. A main observation reveals the striking presence of the art of busking and an imbalance in the representation of modern and traditional art forms. Essentially, the representation of traditional arts was limited and those artists struggled to keep up with their more modern counterpart. Technology, namely, social media, has been identified to have played a major role in influencing this outcome and contributing to this scenario. Management wise, the lack of cooperation from business entities (i.e., premise operators and owners) in support of the local artists, performers, small and medium enterprises, and the event itself is a cause for concern as this has caused several setbacks which were detrimental to the festival’s operations. Hence, the art-based and managerial issues identified in this review may benefit the relevant stakeholders in its decision-making of the festival’s future cycles.